Strategy to Maintain Customer Loyalty at PT Sun Life Financial Unit Syariah Medan Branch - Anisa Rahmadhani; Rahmi Syahriza (Journal of Indonesian Management, 2022)
Loyalty is a customer's attachment to a product or service, measured by repeat purchases. Customer loyalty has an important role in the company. Maintaining them means improving financial performance and maintaining the viability of a company. This is the main reason for a company to attract and retain customers. The purpose of this study was to determine the agent's strategy in forming customer trust and loyalty towards repurchase intentions. To clarifyy thesee problems in depth and comprehensively, the researchers used qualitativee researchh withh data colllection methods inn thee formm of interviews andd observations. Basedd onn thee resultss of the studyy indicate thatt thee strategy to maintain customer loyalty at PT Sun Life Financial Unit Syariah Medan Branch can be said to be in accordance with the strategy in general. But in reality there are several strategies that fail to maintain customer loyalty.